2016
DOI: 10.1016/j.alcohol.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol intake leads to structural and molecular alterations in the rat endometrium

Abstract: We described the effects of low- and high-dose ethanol intake on the structure and apoptosis signaling of the uterine endometrium of UChA and UChB rats (animals with voluntary ethanol consumption). Thirty adult female rats, 90 days old, were divided into three groups (n = 10/group): UChA rats fed with 10% (v/v) ethanol ad libitum (free choice for water or ethanol) drinking < 1.9 g/kg/day; UChB rats fed with 10% (v/v) ethanol ad libitum (free choice for water or ethanol) drinking from 2 to 5 g/kg/day; control r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This finding is consistent with a study conducted by J Lyngsø et al in which they also identified shorter cycles among women abstaining from alcohol, associating these alterations with the fact that alcohol exposure can produce alterations in the hormonal system [ 47 ]. In addition, studies in rats have associated chronic alcohol consumption with endometrial changes and reproductive disorders [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a study conducted by J Lyngsø et al in which they also identified shorter cycles among women abstaining from alcohol, associating these alterations with the fact that alcohol exposure can produce alterations in the hormonal system [ 47 ]. In addition, studies in rats have associated chronic alcohol consumption with endometrial changes and reproductive disorders [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found alterations in the female and male reproductive organs in the high drinkers' group. Studies noticed an irregularity in the estrous cycle, reduction of LH and FSH, follicular atresia, and damage in uterine endometrial cells in drinkers, with effects related to the dose consumed (Chuffa et al 2009, Martinez et al 2016. Acetaldehyde and oxidative stress increase and impairs to HPG/HPA axes are mechanisms that change reproductive hormones balance and, consequently, uterine and ovarian tissues (Buthet et al 2003, Rachdaoui & Sarkar 2017.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted July 18, 2021. ; https://doi.org/10.1101/2021.07.16.452713 doi: bioRxiv preprint a voluntary model of ethanol exposure, UCh rats, avoiding the stress associated with forced feeding and providing knowledge about the effects of voluntary ethanol consumption as observed in society (Gapp et al 2014, Martinez et al 2016).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were housed in polypropylene cages (32 cm × 40 cm × 18 cm) and maintained under controlled conditions (25 ± 1°C, humidity 55 ± 5%, and light from 6 to 18 h) with access to commercial feed and water ad libitum . We employed a voluntary model for ethanol exposure, UCh rat strain, avoiding the stress associated with forced feeding and providing knowledge about the effects of voluntary ethanol consumption as observed in society ( Gapp et al 2014 , Martinez et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%